2022
DOI: 10.1016/j.athoracsur.2021.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Thymectomy for Thymomas: A Retrospective Follow-up Study in the Netherlands

Abstract: BACKGROUND The Maastricht University Medical CenterD is a Dutch center of expertise appointed by the Netherlands Federation of University Medical Centers for the treatment of thymomas. The aim of this study was to investigate the long-term oncologic, surgical, and neurologic outcomes of all patients who underwent a robotic thymectomy for a thymoma at Maastricht University Medical CenterD.METHODS We retrospectively analyzed the clinical-pathologic data of all consecutive patients with a thymoma who underwent ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…6,7 On the other hand, other authors 8,9,13 did not consider any threshold diameter of minimally-invasive thymectomy and they consider every patients suitable for minimally-invasive thymectomy, excluding those with vascular invasion on the superior vena cava, brachiocephalic vein and aorta. Data regarding RATSthymectomy are weak on this argument, but previous published paper 10,[21][22][23] reported the safety and effectiveness of RATSthymectomy also for large lesions. In our practice, we select…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 On the other hand, other authors 8,9,13 did not consider any threshold diameter of minimally-invasive thymectomy and they consider every patients suitable for minimally-invasive thymectomy, excluding those with vascular invasion on the superior vena cava, brachiocephalic vein and aorta. Data regarding RATSthymectomy are weak on this argument, but previous published paper 10,[21][22][23] reported the safety and effectiveness of RATSthymectomy also for large lesions. In our practice, we select…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other authors 8,9,13 did not consider any threshold diameter of minimally‐invasive thymectomy and they consider every patients suitable for minimally‐invasive thymectomy, excluding those with vascular invasion on the superior vena cava, brachiocephalic vein and aorta. Data regarding RATS‐thymectomy are weak on this argument, but previous published paper 10,21–23 reported the safety and effectiveness of RATS‐thymectomy also for large lesions. In our practice, we select patients for RATS‐thymectomy independently to the diameter at the preoperative CT‐scan, but we based our choice on the location of the thymoma and on the absence of an invasive behaviour on the vascular structure of the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…An assistant suction device can be used between the camera port and left arm port if necessary. A right-side approach has a wider field of view and larger working space [ 14 , 15 , 16 , 17 , 18 , 19 ], whereas a left-side approach potentially accesses more thymic tissue and allows easier visualization of the contralateral phrenic nerve [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Although it is controversial whether a left-side or right-side approach is better, several recent studies have reported using the left-side approach for extended thymectomy in patients with MG because it provides enhanced visualization and reduces the probability of phrenic nerve injury [ 21 , 25 , 27 , 28 ].…”
Section: Anterior Mediastinal Tumormentioning
confidence: 99%
“…Historically, the anterior mediastinum was approached through sternotomy, and therefore performed in many (cardio)thoracic surgery centers in the Netherlands. However, due to the relatively low incidence of anterior mediastinal masses and the advent of subspecialized minimally invasive and robotic surgery, thymic and mediastinal surgery can now be considered complex care and is only performed in selected centers; tertiary centers perform surgery of advanced thymoma (Masaoka stages > III) and mediastinal tumors ( 45 ), whereas high-volume secondary centers conduct resections of low-grade thymoma (Masaoka stages I–III) and mediastinal tumors. In these medical centers, a minimally invasive approach, either thoracoscopically or robotically, is now standard of care.…”
Section: Performance Of Dutch Thoracic Surgery Centersmentioning
confidence: 99%